Asian Americans' Emerging Racial Identities and Reactions to Racial Tension in the United States. Issue 2 (April 2022) - Young, Jennifer L.; Li, Grace; Golojuch, Laura; Kim, Haedong
Asian Americans hold a complex racial position in the U.S. They have been considered "honorary Whites, " unaffected by racial discrimination while simultaneously viewed as perpetual foreigners in their homeland. This study was conducted in the context of a historic uprising against racism and police brutality. Semi-structured interviews with 12 Asian American emerging adults explored how participants defined "Asian American" and their position in sociopolitical dialogue. An inductive/deductive thematic approach revealed: participants (1) challenged a monolithic Asian American identity, (2) experienced discrimination and stereotyping related to anti-Muslim sentiments, the "perpetual foreigner" stereotype, and the model minority myth, and (3) described a lack of visibility and representation of Asian Americans in the racial dialogue. In this time of increased racial tension, Asian American emerging adults face discrimination and stereotyping due to misconceptions about Asians. Participants demonstrated active engagement in racial meaning making and found solidarity in relationships with other racial minorities.